Airfield and Highway Pavements 2015 2015
DOI: 10.1061/9780784479216.076
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Estimating the Influence of Soil Suction on the Resilient Modulus of Pavement Subgrade Soils

Abstract: A new approach is proposed in this paper for estimating the resilient modulus (M R ) of pavement subgrade soils taking account of the influence of the soil suction (ψ). This approach includes two steps: step (i) estimating the soil-water characteristic curve (SWCC) using one-point method, and step (ii) predicting the M R -ψ relationships using a simple model and the estimated SWCC from step (i). Estimations of the SWCC and the M R for two different subgrade soils using (i) the proposed approach, and (ii) the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some researchers have shown that the effect of variation of suction value on the mechanical behaviours of compacted granular materials could be related to the variation of water content (Cary & Zapata, 2011;Han, Mihambanou, & Vanapalli, 2015;Ho et al, 2014a;Kolisoja, Saarenketo, Peltoniemi, & Vuorimies, 2002;Nowamooz et al, 2011;Salour, Erlingsson, & Zapata, 2014;Yang, Lin, Kung, & Huang, 2008).…”
Section: Suction Of Unsaturated Soilmentioning
confidence: 99%
“…Some researchers have shown that the effect of variation of suction value on the mechanical behaviours of compacted granular materials could be related to the variation of water content (Cary & Zapata, 2011;Han, Mihambanou, & Vanapalli, 2015;Ho et al, 2014a;Kolisoja, Saarenketo, Peltoniemi, & Vuorimies, 2002;Nowamooz et al, 2011;Salour, Erlingsson, & Zapata, 2014;Yang, Lin, Kung, & Huang, 2008).…”
Section: Suction Of Unsaturated Soilmentioning
confidence: 99%
“…Several researches have shown that besides the effect of water content on the mechanical behaviours of the unsaturated granular materials, it is necessary to take into account the effect of suction (Yang et al 2008, Cary & Zapata, 2011, Nowamooz et al 2011, Nowamooz et al 2013, Salour et al 2014, Han et al 2015and Jing et al 2016, 2017 as well as hydraulic hysteresis (Miller et al 2008, Yang et al 2012and Ho et al 2014). Different experimental researches showed that the variation of fine content (particles passing the sieve 75 µm or sieve No.200 based on American classification) has also an important effect as well as water content on mechanical behaviours of granular materials as reported by Babić et al 2000, Duong et al 2013and Jing et al 2016, 2017 However, the relationship between resilient strain behaviours and unsaturated state with different fine contents has been rarely studied.…”
mentioning
confidence: 99%